STS-768 multiplexer with full-rate output data retimer in InP HBT. - Hendarman, A. (IEEE Journal of solid state circuits)
A 16:1 STS-768 multiplexer IC has been designed and fabricated using the Vitesse Semiconductor VIP-1 process. This IC is part of a complete chip-set solution for a 40-Gb/s STS-768 optical communication transceiver module. The multiplexer IC features a full-rate clock multiplication unit and a data retimer in the output stage to reduce duty-cycle distortion and jitter in the output data eye. Because of its strict timing requirements, this approach needs fast logic gates with a very low gate delay. The Vitesse VIP-1 process, with 150-GHz ft and 150-GHz fmax heterojunction bipolar transistor, is an obvious choice to implement this IC. The multiplexer IC typically dissipates 3.6 W from -3.6-V and -5.2-V power supplies. This paper discusses the design and development of a 40-Gb/s 16:1 multiplexer IC including current-mode logic gate circuit design, divide-by-two, 40-GHz clock tree, voltage-controlled oscillator, clock multiplication unit, and output driver. Layout design and package design are also discussed due to their significant roles in the IC performance.